Implementing Visual Media Based on Local Wisdom to Improve Students’ Learning Outcomes - Fatmi, Nuraini; Fauzan, Fauzan; Setiawaty, Sri; Fakhrah, Fakhrah (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to examine the effect of implementing visual media based on local wisdom on students' learning outcomes at SMAN 6 Lhokseumawe. The background of this research is grounded in the importance of using instructional media that is contextual, engaging, and relevant to the students’ cultural environment. This research employs a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects consisted of students in class XI A as the experimental group and XI B as the control group, with 30 students in each class. The instruments used included pretest and posttest assessments to measure students’ learning outcomes, as well as observation sheets to support data on classroom activities. The analysis results showed that the average posttest score of the experimental class (82.7) was higher than that of the control class (71.3). The t-test results indicated a significance value (p) of 0.003 0.05, which means there was a statistically significant difference between the two groups. Therefore, visual media based on local wisdom proved to be effective in enhancing students' learning outcomes. Instructional media that incorporates local cultural elements not only improves cognitive understanding but also strengthens students’ identity and character values. Accordingly, the use of local wisdom-based media is recommended to be integrated into the school learning process.